Analysis of Bride Trafficking Activities From Pakistan to China in 2018 - Syafiiqoh, Nabiilah Hanuun; M. Riza Hanafi (Department of International Relations, Universitas Brawijaya, 2025)
This research examines bride trafficking activities from Pakistan to China in 2018. Bride trafficking itself is commonplace in both countries. From the Pakistani side, bride trafficking is still related to the practice of forced marriage. Meanwhile, from China's side, bride trafficking is the impact of the implementation of the one child policy, which will result in a population decline in the future. The cost of preparing a wedding dowry in China is high, so men, especially from rural areas of China, consider it cheaper to illegally